Automatic Balancing Time of any Rotors at Full Speed; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Pashkov E. N. Evgeny Nikolaevich (Materials Processing Technologies in Mechanical Engineering, 2014)
Title screen